What makes the systems engineer successful? various surveys suggest an answer - Eisner, Howard, 1935- (Boca Raton : CRC Press, 2020)
This book offers a survey of successful attributes of the systems engineer. It focuses on the key positive attributes of what today's systems engineer should be and puts a model in place for achievement and behavior for future systems engineers. The book, in survey form, provides a description of how and why systems engineers can be, and have been, successful. It offers successful attributes, focuses on the key positive qualities, and drills down to the success features to aim for and the failure characteristics to avoid. The ending result is that it sets a model for achievement and behavior for future systems engineers to follow a successful path. This book will be helpful to systems engineers, industrial engineers, mechanical engineers, general engineers, and those in technical management.
1 Systems Engineering: No Room at the Top 2 Selected Best Systems Engineers 3 Synthesizer 4 Listener 5 Curious/Systems Thinker 6 Manager/Leader 7 Expert/ESEP 8 Expert/Domain Knowledge 9 Perseverer 10 Recapitulation Appendix A -- INCOSE Fellow Inputs Appendix B -- Across the Board Articles Index
OCLC-licensed vendor bibliographic record.
Keywords: Systems engineering -- Vocational guidance; Occupational surveys; TECHNOLOGY / Engineering / General; TECHNOLOGY / Manufacturing; TECHNOLOGY / Industrial Design / General